Peran Bahasa Ibu dalam Penguatan Pendidikan Karakter pada Pembelajaran Bahasa Indonesia di Kelas Rendah SDN 016532 Punggulan - M. Indrawan; Nia Asti Ramadhani; Khairunisa Marpaung; Keyla Putri; Nadia Bismi Hafifah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the role of mother tongue in strengthening character education in Indonesian language learning in the lower grades of SDN 016532 Punggulan. This study uses a qualitative approach with a descriptive type. Research data were obtained through observation, in-depth interviews with the principal and teachers, interviews with students in grades I, II, and III, and documentation. Data analysis was conducted using the Miles and Huberman model through the stages of data condensation, data presentation, and drawing conclusions. The results show that the mother tongue is used by teachers as a supporting communication medium to help students understand learning materials and adapt to the use of Indonesian as the language of instruction in schools. The proportional use of the mother tongue creates a more comfortable learning atmosphere, supports students' courage in communicating, and makes it easier for teachers to instill character values ​​such as discipline, responsibility, cooperation, honesty, and politeness. This study also found that the diversity of students' language backgrounds is a challenge that needs to be managed through appropriate learning strategies. Thus, the targeted use of the mother tongue can be a contextual learning strategy to strengthen character education without reducing the role of Indonesian as the main language of instruction.